The Impacts Of Autonomous learning on English Vocabulary Learning: Virtual Environtment - M. Farkhi Faishol Hakim (Department of English Language Education, UIN Sunan Ampel Surabaya, 2021)
There are many differences in sentence structure between English and Indonesian. In this study, the researchers conducted a comparative analysis of past sentence patterns in English and Indonesian. The purpose of this research is to find out the past sentence patterns of English and Indonesian, and the similarities and differences between them. The methods used to conduct research are qualitative research and descriptive research to compare patterns between English and Indonesian past sentence patterns. A high school textbook named